Pengaruh Penggunaan Media Berbasis Information Technology Pada Pembelajaran IPA Terhadap Prestasi Belajar Ditinjau Dari Kemandirian Belajar - Lestari, Endang; Sunardi, Sunardi; Suryani, Nunuk (Teknodika, 2017)
The purpose to be achieved in this research is to know; 1) differences in the influence of the use of media ICT and conventional learning against learning achievement in grade V Diponegoro Cluster Elementary Schools, 2) the difference between the effect of learning independence in the high and low categories of the learning achievement of students in grade V Diponegoro Cluster Elementary Schools, 3) the interaction of the use of ICT media and learning independence on the learning achievement of the students of grade V Diponegoro Cluster Elementary School. This type of research uses the 2x2 Factorial Experimental Method. The research population was all elementary school students of grade V Diponegoro Cluster Elementary School, Bae sub-district, Kudus. The research is using Random Sampling Clusters, Selected SDN 2 Dersalam and SDN 1 Dersalam. Data collection techniques is using questionnaire and test. Hypothesis testing is using Two Path ANAVA Technique. The results of the study are: 1) there is significant differences in the influence of ICT learning media and conventional learning on science learning achievement (Fcount 4,808> Ftable 4,000), 2) there is significant differences in the effect of learning independence on science learning achievement (Fcount 4,770> Ftable 4,000), and 3 ) there is a significant influence of learning media interaction and learning independence on science learning achievement (Fcount 4.402> Ftable 4,000)